Gait abnormalities before and after total hip arthroplasty differ in men and women. Issue 14 (3rd October 2016) - Foucher, Kharma C.
Abstract: This study tested the hypothesis that men and women have different preoperative and postoperative gait impairment relative to sex-matched healthy controls, and that the extent of gait improvement after total hip arthroplasty (THA) is different between men and women. A group of 124 THA subjects was identified from a motion analysis data repository; age and BMI-matched male and female control groups were then identified from the same repository. Dynamic sagittal plane hip range of motion (HROM) and peak 3D external moments at subjects' normal walking speeds were analyzed. Each hypotheses was tested using linear regression models, to adjust for potential confounding effects of walking speed. Preoperatively, the THA vs. control group differences in the HROM and peak adduction moments were larger in women than they were in men ( p =0.007). The THA group vs. control group difference in the peak external rotation moment was larger in men ( p =0.004). After surgery, HROM increased more in women than in men ( p =0.020). However, peak adduction moment decreased in men but increased in women (−0.11±0.93 vs. 0.28±1.3%BWH, p =0.045). Accordingly, postoperatively the THA group vs. control group differences in the peak external rotation moment remained larger in men than in women ( p =0.016). There were no other sex-specific differences ( p =0.072–0.876). This study suggests that men and women have slightly different patterns of gait recovery after THA and may benefit from sex-specific rehabilitation strategies. These differences also underscore the importance of accounting for sex in biomechanical studies.